Actitudes de psicólogos y psiquiatras sobre pacientes con el trastorno límite de personalidad en un hospital psiquiátrico de Lima, Perú - Pérez Luna, Paolo (2016)
Borderline Personality Disorder (BPD) is a severe mental disorder, high incidence in clinical population, the current treatment is basically psychotherapeutic and therapistpatient relationship is essential for development. The main problem was defined as what are the attitudes of psychology and psychiatrists in patients on borderline personality disorder in a psychiatric hospital in Lima, Peru, in which there is no history of such research in that country. The research is not experimental and applicative with cross-sectional design and the level is descriptive. The instrument used is a Likert scale of 33 questions, a questionnaire created for purposes of this investigation. The sample was chosen randomly. The sample size was calculated using the formula of finite populations, quantifying it in 47 participants. The results with the SPSS statistical program was evaluated using Chi2 statistical formula. A third of the sample considered manipulative behavior as an important symptom for the diagnosis, especially during hospitalization. Most professionals recognize that the attitude towards these patients is different from other patients with other diagnoses. Feelings of frustration and emotional exhaustion are common among professionals. Psychologists were more unfavorable cognitions about the BPD compared with psychiatrists.